Analisis Persepsi Jemaat GKPPD Sangga Beru tentang Fondasi Pernikahan dalam Mewujudkan Keluarga Harmonis - Sry Nola Manik (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This study aims to analyze the perceptions of the congregation of GKPPD Sangga Beru regarding the foundation of marriage in building a harmonious family. In Christian teachings, marriage is not just a bond between two individuals, but a divine institution designed to form a family based on faith, love, and mutual trust. However, factors such as the wrong foundation in marriage, economic problems, poor communication, and cultural pressures often threaten family harmony.Using a descriptive approach, this study identified the congregation's perceptions of the foundation of marriage and the factors that cause disharmony in the household. From the results of interviews with 10 informants, it was found that the three main foundations of Christian marriage are faith in Jesus Christ, loving and caring for each other, and trusting each other. Faith serves as a foundation in facing various life challenges, while love ensures emotional warmth, and trust binds couples in joy and sorrow.However, the results of the analysis also show that some couples marry for reasons of matchmaking, social influence, or simply to have children, which often triggers conflicts such as lack of understanding between partners, lack of trust, comfort, openness, and problems related to the presence of children. In an effort to create a harmonious family, values ​​such as mutual understanding, open communication, and cooperation are very important. The church plays a crucial role in guiding the congregation through faith teachings and counseling services. However, in GKPPD Sangga Beru, the lack of an effective counseling program is an obstacle in providing optimal support to couples in facing the challenges of marriage.